Demotivated Students during Online English Learning in Covid-19 Pandemic: Voices from Indonesian Students - Pratama, Achmad Hendy; Primary, Metty Agustine; Dewi, Nita Sari Narulita (Universitas Siliwangi, 2022)
The COVID-19 pandemic has forced all sectors to stop their activities. As a result of this, learning activities were suddenly changed to online methods. Seeing the phenomena that occur around researchers, the decreasing of students' motivation during online English learning can be a serious matter. If the demotivating factor cannot be known, it will be difficult for the teacher to overcome it. To fill this gap, the researcher intends to look for the factors that cause demotivation in students during online English learning. An exploratory case study was employed as the research design and semi-structured interviews were selected as the data collection technique. The data were analyzed using thematic analysis based on demotivating factors (learning contents and materials, teachers’ competence and teaching styles, inadequate school facilities, and lack of intrinsic motivation). Research reveals that there are two major factors of demotivation experienced by students: (1) internal factors; (2) external factors. Internal factors consist of lack of interest; undirected study goals; negative habits, and external factors consisting of surrounding elements; teaching style; teaching materials and teaching content; learning facilities; sudden transition. In conclusion, the teaching and learning practices should encourage students to have positive experiences and not demotivate them in learning English such as using interesting online tasks.